The role of video and direct laryngoscopy in medical student intubation training: a comparative study on success rates and learning curves - Mustafa Öcal (BMC Medical Education)
Abstract Background Direct laryngoscopy (DL) is widely recognized as the most commonly used method for tracheal intubation. However, growing evidence highlights the increasingly prominent role of video laryngoscopy (VL) in the management of difficult airways. This study aimed to determine the most effective medical education method to equip medical students with this critical skill. In addition to evaluating the contributions of an intubation training program utilizing direct laryngoscopy and video laryngoscopy to tracheal intubation success among inexperienced medical students, we also aimed to explore the potential benefits of combining these two techniques. Methods This mannequin-based study included 130 medical students. Before the study began, participants attended a 30-minute theoretical training session. Participants were randomly assigned to start with one of two scenarios. In each scenario, participants were given three attempts to perform intubation using each laryngoscope. The maximum allowable time for each intubation was set at 3 min. Students who successfully intubated within 3 min were recorded as successful, while those who failed to do so were recorded as unsuccessful. Results The study demonstrated that VL provided higher success rates and shorter intubation times, particularly during the first and second attempts. However, it is noteworthy that no significant difference in success rates was observed between VL and DL during the third attempt. Conclusion This study highlights the necessity of integrating both VL and DL methods in intubation training programs. The combination of both approaches allows students to achieve quick initial results while progressively developing proficiency for more complex scenarios over time. Clinical trial number Not applicable.